ASSOCIATION OF HLA AND CYTOKINES OF BLOOD WITH ANTIINFLAMMATORY EFFECTS IN PATIENTS WITH CHRONIC GLOMERULONEPHRITIS - Kolesnyk, M.; Driyanska, V.; Drannik, G.; Petrina, O.; Velychko, M.; Nepomnyaschiy, V. (Ukrainian Journal of Nephrology and Dialysis, 2017)
Cytokines and HLA take important part in immunogenesis of many diseases, therefore the analysis of these indices and this associations in dependence of glomerulonephritis (GN) can define their value as the additional prognostic markers. Aim of the work is to determine the of associations the high serum levels of cytokines (IL-4, IL-17) and peculiarities of some HLA in phenotype to substantiate of chronic glomerulonephritis with nephrotic syndrome (CGN, NS) immunogen- esis and to ascertain the additional prognostic markers. Materials and methods. There was studied the HLA-antigens distribution in the 264 adult patients CGN, NS (the diagnosis was confirmed morphologically using the thin needle nephrobiopsy) and 350 healthy donors by typing the lymphocytes with the aid of standard microlymphocytotoxic test (Terasaki’s test). HLA antigens were defined using a standard microlymphocytotoxic test on the Terasaki’s planchette with special panels ofanti-HLA serums (20 antigens of locus A, 31 - B and 9 - DR). The etiologic fraction (attributive risks ) was counted using the formula: ct = x - y/I - y, where x - frequency of antigen in patients and y - frequency in healthy. The ct reading was considered significant when it exceeded 0,1. Using ELISA, the level of the cytokines was studied in the blood serum - IL-4 in 76 and IL-17 – 79 patients. Results. HLA-A23, -24, -28, -B8, -38, -41, -44, DR1, -4, -w52 in adults patients have associations (RR>2) CGN, NS; the attributive risk (AR) (<j>0,1) to develop GN detected in patients have A24, A28, B8, DR 1, 4, w52. The CGN, NS patients has statistically higher serum level of the IL-4 and IL-17, with more high indices of this cytokines in patients with attributive risk antigens HLA-A24 and A-28. The highest levels of IL-17 detected also in adults case have B14 and B38, which associated with steroid sensitive NS. HLA-B8, which associated with steroid resistant NS, have more patients with CGN, NS with lower serum level of antiinflammatory IL-4. Conclusion. The patients with CGN, NS have associations of HLA and serum levels of pro- and antiinflammatory cytokines IL-4 and IL-17, which play role of additional prognostic predictors.